How to Set Up Central Isolation Sites to Prevent Re-outbreaks From Imported Cases of COVID-19: The Experience of Shanghai, China. (4th June 2022) - Zhang, Wei; Ge, Zhiru; Lu, Jide; Wang, Hairong; Yang, Yawei
Abstract: As strict measures were taken, the coronavirus disease 2019 (COVID-19) epidemic has been gradually brought under control. As a port city, Shanghai's main problem has shifted from treating local cases to preventing foreign imports. To prevent the re-outbreak of COVID-19 caused by imported cases, the Shanghai government has set up central isolation sites for all people entering the country from abroad to be placed under medical observation. This report describes how to set up central isolation sites and run them effectively. We put isolation sites in transformed hotels, arranged personnel according to a huge data network, and set up specific procedures to manage guests. The epidemic situation in Shanghai has confirmed the feasibility and effectiveness of the methods that other jurisdictions can adapt for their use.